18 Moderate alcohol consumption is associated with progression of left ventricular dysfunction in pre-heart failure. (6th October 2022) - Wong, B; Moore, A; Radhakrishna, A; McDonald, K; Ledwidge, M
Abstract : Background: There is limited evidence of the longitudinal impact of alcohol use and progression of structural cardiac changes amongst European populations at risk of heart failure (CV risk factors) or with pre-heart failure (asymptomatic but with cardiac changes, and no previous heart failure [HF]). Furthermore, the 2021 European guidelines describe beneficial effects in the general population of light alcohol (<140 g/week for men and <70g/week for women) usage on risk of HF, despite contrary emerging evidence. Aim: To understand the dose-response relationship between alcohol consumption and progression of pre-HF in a European population. Methods: This is a secondary analysis of the St Vincent's Screening TO-Prevent Heart Failure (STOP-HF) trial amongst patients who are at risk of HF or with pre-HF, with documented alcohol intake and echocardiography at both baseline and follow up ≥18 months. Excluded were ex-drinkers and patients with symptomatic HF. The main outcome measure was the relationship between progression of cardiac functional changes (progression of pre-HF) or onset of symptomatic HF, stratified according to whether patients were classified as at risk of HF or with pre-HF at baseline, and 3 categories of alcohol dose: no alcohol usage; low alcohol use (up to 1 unit daily or 70g/week); moderate-high alcohol usage (>1 unit daily or >70g/week). Progression of pre-HF was defined as follow up left ventricular dysfunction (EF <50%) and a decline of at least 5% and/or lateral E/e' >13 increase of at least 2 units. Prespecified covariate adjustment included age, gender, obesity, hypertension, diabetes and vascular disease. Results: Of 744 patients included in the analysis (mean age 66.5 (9.8) years), 395 (53.1%) were female, 556 (74.7%) had hypertension, 145 (19.5%) had diabetes and 260 (34.9%) had pre-HF at baseline. Overall, a total of 201 (27.0%) patients reported no alcohol usage, 356 (47.8%) reported low (≤70g/ wk) alcohol intake and 187 (25.1%) reported moderate-high alcohol usage with >70g/wk alcohol intake. There was no difference in reported alcohol usage between those at risk of HF and pre-HF patients. Those with moderate-high alcohol usage were younger, more likely to be male and had higher body mass index than patients with low alcohol usage. Over a median follow up period of 5.44 [IQR 4.33;6.73] years, 84 (11.3%) patients had progression of pre-HF or developed symptomatic HF. Moderate-high alcohol usage was associated with an adjusted 4.5 fold (95% CI 1.7- 15.9, p=0.004) increased risk of progression of pre-HF/HF amongst those with pre-HF at baseline compared to those who reported no alcohol intake. ( Figure 1 ) Increased HF progression was also evident in moderate (70–140g/week) and high (>140g/week) alcohol use subgroups. Conversely, in patients at risk of HF, at baseline had no association of moderate-high alcohol usage with progression of HF. Finally, there was no protective associations of low alcohol usage (<70g/week) and progression of HF in any patient group. Conclusion: Moderate alcohol (>70g/week; more than 1 bottle of 12.5% wine/week) usage appears to be associated with progression of pre-HF and HF in European patients in the STOP-HF study ( figure 1 ) and we did not observe protective benefits of low alcohol usage. These data are in accordance with recent evidence from Asian populations. European HF guidelines should reconsider advice suggesting any protective effects of alcohol on risk of heart failure.